Ergonomic Design Improves Cross-Cultural Road Sign Comprehension. (April 2021) - Ben-Bassat, T.; Shinar, D.; Caird, J.K.; Dewar, R.E.; Lehtonen, E.; Sinclair, M.; Zakowska, L.; Simmons, S.; Liberman, G.; Pronin, M.
Highlights: Road sign comprehension is a persisting international problem. This study compared comprehension of alternative sign designs in five countries. Ergonomics-based alternatives were generally superior to conventional signs. Comprehension correlated well with ratings of the same signs by ergonomics experts. Applying ergonomics criteria can improve comprehension of new and existing signs. Abstract: Background: Traffic sign design can have a substantial impact on road safety and traffic flow. The current study had three objectives: 1) Cross-validate the importance of ergonomic sign design; 2) Evaluate the ability of ergonomics experts to predict sign comprehension by the average driver; 3) Offer improved sign designs for poorly designed road signs. In a previous study (Ben Bassat et al., 2019), human factors and ergonomics experts evaluated several alternative designs for 31 different road signs, based on three ergonomics criteria – familiarity, standardization, and message/symbol compatibility. Some of these signs were tested in the current study and the correlation between the results of the two studies was analyzed. Method: In this study, 805 licensed drivers from five countries were tested on their comprehension of 24 conventional signs and 32 alternative signs. Signs were individually presented on a screen and as soon as the participant decided on the meaning, the sign disappeared, and an experimenter wrote the stated meaning. The verbal responses were coded as correct (perfectly or partially), wrong, or opposite of the true meaning. Sign identification response time was also recorded. Results: In all countries across all signs, more drivers comprehended the alternative ergonomically superior signs, and the identification response times were shorter for these sign designs. Furthermore, the correlation between ergonomics experts' ratings as found in previous study and the percent of comprehension for each sign design was statistically significant and positive with r = 0.61. Conclusions: Road signs should be designed according to ergonomics-based criteria. Human factors experts' opinions can be a useful tool in improving the design of poorly comprehended signs (or icons) and in designing new signs (or icons).